2014
DOI: 10.1186/1752-1947-8-367
|View full text |Cite
|
Sign up to set email alerts
|

Septic arthritis caused by Brucella melitensis in urban Shenzhen, China: a case report

Abstract: IntroductionBrucellosis is a systemic infectious disease which is still a challenging medical problem in rural areas such as northern China. It rarely occurs in urban areas such as Shenzhen in southern China. Osteoarticular involvements are frequently seen in brucellosis, and rarely is arthritis the only clinical presentation. We report a case of hip septic arthritis caused by Brucella melitensis in an urban area of Shenzhen, China.Case presentationA 29-year-old Chinese woman, Han ethnical group presented to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 15 publications
1
13
0
1
Order By: Relevance
“…Besides the above endemic areas, there is recently an increase in trend of human brucellosis in southern provinces, such as Henan, Guangdong, and Fujian [4]. Retrospective studies in northern China were commonly reported [5,6], yet similar studies were limited in southern China [7,8]. This retrospective study aims to include a case series of brucellosis in Shenzhen, a Southern Chinese cosmopolitan city with over 20 million population including a large immigrant population from other parts of China, and to describe the clinical features and epidemiology of this disease in Shenzhen.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the above endemic areas, there is recently an increase in trend of human brucellosis in southern provinces, such as Henan, Guangdong, and Fujian [4]. Retrospective studies in northern China were commonly reported [5,6], yet similar studies were limited in southern China [7,8]. This retrospective study aims to include a case series of brucellosis in Shenzhen, a Southern Chinese cosmopolitan city with over 20 million population including a large immigrant population from other parts of China, and to describe the clinical features and epidemiology of this disease in Shenzhen.…”
Section: Introductionmentioning
confidence: 99%
“…An outbreak of human brucellosis in Jiangsu province (southern province in China) was due to the plentiful influx of unchecked sheep from the northern part of China and lack of effective prevention programmes (Xiang et al., ). Another brucellosis case reported in Shenzhen was proved to exposure to fed lambs (Wong et al., ). Reported human brucellosis caused by occupational exposure in farm or slaughter house has been documented, and epidemiological features were described in previous studies (Shalmali et al., ; Amira et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…2 Wong y col. informaron artritis séptica por Brucella en la cadera, mientras que Kalkan y col. informaron esta afección en la rodilla. 12,13 En este estudio, hubo un caso de artritis séptica.…”
Section: Discussionunclassified